Comparative Resource Use Optimality Among Selected Irrigated Maize Farmers In The North Western States Of Nigeria: A Dea Approach - Abiodun, Ajiboye; Olayinka, Osundare F. (Advances in Social Sciences Research Journal, 2017)
The study examined resource use optimality in 240 irrigated maize farms sampled from four states of North-western Nigeria. Data Envelopment Analysis (DEA) was employed to obtain three types of optimality – optimal, sub optimal and super optimal output levels. The results show that there were substantial scale inefficiencies in all the four states. This implies that most of the farms should be larger than their present sizes in order to achieve higher production given, the available factor mix.. The results also showed that If all farms were using the same technology, then it would be expected that return to scale would increase for farms with a relatively low outputs and decreasing return to scale farms with a relatively high outputs .Constant return to scale would be expected for farms with output levels equal to the mean output .The mean output of the suboptimal scale is larger than the mean output of the optimal as well as super optimal scales for Kebbi State. In the remaining three states, and the pooled data, the mean outputs of the super – optimal scale were large than the mean outputs of the optimal and sub-optimal scales. Farms that are characterized by constant return to scale can change scale of operation only by proportionately increasing or decreasing input-output combinations. Those that were characterized by increasing return to scale can gain efficiency by increasing production and become scale efficient. On the other hand, those found to be operating in the decreasing return to scale range, would need to reduce scale of operation to gain efficiency improvements.